Comparative evaluation of the apical leakage of different bioceramic retrofilling materials with and without smear layer: A stereomicroscopic study - Sheikh Shahbaz; Huma Iftekhar; Sharique Alam; Surendra Kumar Mishra (Indian Journal of Dental Research, 2022)
Objective: Present in-vitro study aimed to evaluate the apical leakage of different bioceramic retrofilling materials with and without smear layer. Materials and Methods: Sixty human single-rooted teeth were decoronated at a standardized root length of 13 mm, chemo-mechanically prepared and obturated. After obturation, root-end resection was done and root-end cavities were prepared using ultrasonic tips. The specimens with prepared retro cavities were randomly assigned into 2 groups (n = 30) based on the smear layer removal protocol used. Each group was further subdivided into 3 subgroups (n = 10) based on the bioceramic retrofilling material MTA (Mineral Trioxide Aggregate; Proroot Dentsply/Tulsa), CEM (Calcium-Enriched Mixture; Bionique Dent, Tehran) and ERRM (EndoSequence® Root Repair Material; Brasseler USA, Savannah, GA). The extension of dye (2% Rhodamine B) penetration was measured in millimetre using a stereomicroscope at 10× zoom. Results were statistically analysed using one-way ANOVA (analysis of variance) test and unpaired Student's t test. Results: In the presence of smear layer, MTA demonstrated maximum mean apical leakage value (1.70 ± 0.30), followed by CEM (1.40 ± 0.37) and ERRM (1.40 ± 0.23), which was statistically not significant. Without the smear layer, ERRM demonstrated the least mean apical leakage value, which was statistically significant as compared with CEM (P <.05) and MTA (P <.01). Conclusion(s): All bioceramic retrofilling materials demonstrated apical leakage irrespective of the presence or absence of the smear layer. The presence of a smear layer is beneficial for the sealing ability of MTA and CEM, whereas, the absence of the smear layer is advocated while using ERRM.